Secure Smart Embedded Devices, Platforms and Applications - Markantonakis, Konstantinos; Mayes, Keith; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
New generations of IT users are increasingly abstracted from the underlying devices and platforms that provide and safeguard their services. As a result they may have little awareness that they are critically dependent on the embedded security devices that are becoming pervasive in daily modern life. Secure Smart Embedded Devices, Platforms and Applications provides a broad overview of the many security and practical issues of embedded devices, tokens, and their operation systems, platforms and main applications. It also addresses a diverse range of industry/government initiatives and considerations, while focusing strongly on technical and practical security issues. The benefits and pitfalls of developing and deploying applications that rely on embedded systems and their security functionality are presented. A sufficient level of technical detail to support embedded systems is provided throughout the text, although the book is quite readable for those seeking awareness through an initial overview of the topics. This edited volume benefits from the contributions of industry and academic experts and helps provide a cross-discipline overview of the security and practical issues for embedded systems, tokens, and platforms. It is an ideal complement to the earlier work, Smart Cards Tokens, Security and Applications from the same editors.
An Introduction to Smart Cards and RFIDs -- Embedded DSP Devices -- Microprocessors & Microcontrollers Security -- An Introduction to the Trusted Platform Module and Mobile Trusted Module -- Hardware and VLSI Designs -- Information Security Best Practices -- Smart Card Security -- Graphics Processing Units -- A Survey of Recent Results in FPGA Security and Intellectual Property Protection -- Mobile Communication Security Controllers -- Security of Embedded Location Systems -- Automotive Embedded Systems -- Analysis of Potential Vulnerabilities in Payment Terminals -- Wireless Sensor Nodes -- Near Field Communication -- The BIOS and Rootkits -- Hardware Security Modules -- Security Evaluation and Common Criteria -- Physical Security Primitives -- SCADA System Cyber Security -- An Overview of PIC Microcontrollers and their Suitability for Cryptographic Algorithms -- An Introduction to Java Card Programming -- A Practical Example of Mobile Phone Application using SATSA (JSR 177) API -- Wireless Sensors(Languages/Programming/Developments/Tools/Examples).
Keywords: Computer science; Computer network architectures; Data protection; Data structures (Computer science).; Telecommunication; Computer Science; Systems and Data Security; Data Structures, Cryptology and Information Theory; Information Systems Applications (incl. Internet).; Computer Systems Organization and Communication Networks; Communications Engineering, Networks